2003
DOI: 10.1037/0735-7044.117.5.927
|View full text |Cite
|
Sign up to set email alerts
|

Oral cocaine seeking by rats: Action or habit?

Abstract: Having established that the presence of cocaine in a 10% (wt/vol) sucrose solution enhanced the reinforcing properties of the solution in a dose-dependent manner, the authors investigated the susceptibility of oral cocaine seeking to outcome devaluation. Rats were trained to perform different instrumental responses for a cocaine-sucrose and a lemon-sucrose solution. An aversion was then conditioned from either the cocaine-sucrose or the lemon-sucrose solution by pairing consumption with lithium chloride. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 44 publications
(54 reference statements)
10
151
3
1
Order By: Relevance
“…The present findings extend those obtained using natural or oral drug rewards (Corbit et al, 2012;Dickinson et al, 2002;Miles et al, 2003) showing that responding that is initially goal directed becomes habitual with overtraining. However, the increasing influence of habits in driving nicotine-seeking does not preclude involvement of other factors in sustaining responding, including the conditioned reinforcing properties of nicotine-paired cues.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present findings extend those obtained using natural or oral drug rewards (Corbit et al, 2012;Dickinson et al, 2002;Miles et al, 2003) showing that responding that is initially goal directed becomes habitual with overtraining. However, the increasing influence of habits in driving nicotine-seeking does not preclude involvement of other factors in sustaining responding, including the conditioned reinforcing properties of nicotine-paired cues.…”
Section: Discussionsupporting
confidence: 70%
“…For this reason, alternative approaches have been employed, including oral drug delivery (Dickinson et al, 2002;Miles et al, 2003) or the use of seeking-taking schedules to provide indirect measures of reward devaluation (Olmstead et al, 2001;Zapata et al, 2010). Although informative, such procedures may be limited as the method and route of administration are critical to the long-term behavioral (Leblanc et al, 2013) and neurobiological (Chen et al, 2008;Stefanski et al, 1999) effects of addictive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, limited access self-administration may fail to produce either robust sensitization or symptoms of addiction, as discussed above. Conversely, sensitizing treatments with experimenter-administered drugs are sufficient to produce increased motivation for drug reward ( Vezina 2004), incentive sensitization of cue wanting (Robinson & Berridge 2000;Di Ciano 2007), cognitive impairment (Schoenbaum & Shaham 2008) and stronger S-R habits (Miles et al 2003;Nelson & Killcross 2006), all of which may contribute to the transition to addiction. In addition, experimenteradministered drug that induces sensitization also changes the brain in ways related to the propensity to relapse, such as enhancing glutamate release in the core of the accumbens (Pierce et al 1996).…”
Section: Does Experimenter-administered Drug Produce Changes In the Bmentioning
confidence: 99%
“…On the other hand, everyone must agree that S-R habits probably contribute to the automatized behaviours and rituals involved in consuming drugs once obtained (Tiffany 1990), and it has been shown that treatment with drugs facilitates the development of S-R habits in animals (Miles et al 2003;Nelson & Killcross 2006), perhaps via recruitment of the dorsal striatum (Everitt et al 2001;Porrino et al 2007). We also note that habits may be especially prominent in standard animal self-administration experiments, where only a single response is available to be performed (e.g.…”
Section: What Is Incentive Sensitization Theory and What Is The Role mentioning
confidence: 99%
“…As such, deficits in S-R learning have the potential to interfere with the ability to respond to the changing consequences of behavior. For example, so-called "habit" learning is one form of S-R learning, whereby learned responses in laboratory animals become resistant to extinction even when the reinforcer that maintained responding to the stimuli has been devalued (see Packard & Knowlton, 2002); in other words, the stimulus comes to elicit the response directly, with no intervening "expectancy" of the outcome (e.g., Miles et al, 2003). Cocaine-dependent individuals report that they continue to take cocaine despite receiving negative consequences in social, emotional and physical realms.…”
Section: Introductionmentioning
confidence: 99%